Customs, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
A picture of Customs Trinidad. In this picture you can see a boat docked and people walking pass the harbour. Affixed to this card is a Trinidad and Tobago three cent stamp. Postcard numbered 6.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Harbors--Trinidad and Tobago; Boats and boating--Trinidad and Tobago; Customhouses--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain